Income Inequalities in the Accelerating Digital Era: Evidence from EU Countries and COVID-Time - Woźniak-Jęchorek, Beata; Kuźmar, Sławomir (Panoeconomicus, 2023)
Many research state that digitalization is mainly an opportunity, now more than ever. Digital firms are more productive, employ more skilled workers, and foresee more employment growth opportunities ahead. In 2020, the combined health and economic shocks have, however, accelerated the technology-driven displacement of jobs, which can exacerbate existing inequalities in the coming years. The goal of this paper is to analyze changes in the scale of income inequalities over the last five years, ending in 2021 with respect to the pre-existing inequalities in access to ICTs (connectivity), differences in digital skills (human capital), integration of digital technology in enterprises and digital public services in EU countries. Our research indicates that in the short-term, the degree of inequality in EU27 nations grew more in countries with greater connectivity, as measured by access to broadband Internet. However, only the integration of digital technology in businesses and fundamental access to the Internet were linked to a greater reduction in the Gini index from 2017-2021. JEL: D31, E24, O33.